Sodium electric layered oxide positive electrode material and preparation method, positive electrode sheet, battery and electric device

CN122916231APending Publication Date: 2026-10-16TIANJIN ZHONGDIAN NEW ENERGY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611034754.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]然而,O3相在充放电过程中会经历复杂的相变行为,伴随较为剧烈的晶胞体积波动,这不利于材料在长期循环过程中的结构稳定性

Benefits of technology

[0020]本发明具有的有益效果至少包括:通过柠檬酸钠原位热分解包覆与碱金属层、过渡金属层双位点掺杂的协同作用,制备出在低电压区间内具备高首周充电比容量、高放电均压及优异循环稳定性的钠电层状氧化物正极材料,有效解决了O3相材料在低电压应用中存在的钠损失、动力学缓慢及结构不稳定等问题,为低温启停等场景提供了高性能正极材料解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916231A_ABST
    Figure CN122916231A_ABST
Patent Text Reader

Abstract

The application provides a sodium battery layered oxide positive electrode material and a preparation method, a positive electrode sheet, a battery and an electric device, and the preparation method comprises the following steps: sintering a sodium battery layered oxide base material in an oxygen-containing atmosphere to obtain a sodium battery layered oxide base material; and sintering the sodium battery layered oxide base material and sodium citrate in an inert atmosphere to obtain a sodium battery layered oxide positive electrode material; wherein the chemical formula of the sodium battery layered oxide base material is Na x M y Ni a Mn b Fe c Q z O2, M is one or more of Ca, K and Li, Q is one or more of Cu, Sn, Mg, Al, Li, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo, W and B, a+b+c+y+z=1, 0.9
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, and in particular to sodium-ion layered oxide cathode materials and their preparation methods, cathode sheets, batteries, and electrical devices. Background Technology

[0002] Sodium-ion batteries have become an important new type of rechargeable battery technology that complements lithium-ion batteries due to their potential advantages in wide-temperature performance, safety, and cost. Among these, the cathode material, as a key component of sodium-ion batteries, directly affects the battery's energy density and cycle life. Among various cathode material systems, layered oxide cathode materials have attracted widespread attention due to their high energy density, fast sodium-ion diffusion kinetics, simple processing, and low cost.

[0003] Layered oxide cathode materials mainly include two types: O3 phase and P2 phase. The structural differences between these two phases determine their varying performance in different application scenarios. Specifically, for practical applications such as low-temperature start-stop, electrode materials need to simultaneously achieve high specific capacity and suitable operating voltage within a relatively low operating voltage range. To address this requirement, from the perspective of intrinsic material properties, O3 phase materials, due to their more stable electrochemical behavior in the low-voltage range, are more suitable for operation in such low-voltage areas than P2 phases. This gives them a certain performance advantage in specific scenarios such as low-temperature start-stop.

[0004] However, the O3 phase undergoes complex phase transitions during charge and discharge, accompanied by significant fluctuations in cell volume, which is detrimental to the structural stability of the material during long-term cycling. Furthermore, although the O3 phase itself has a higher sodium content than the P2 phase, during the first charge and discharge cycle, a portion of sodium ions will inevitably be irreversibly consumed due to the formation of the solid electrolyte interphase (SEI) film on the negative electrode surface. This sodium loss directly reduces the actual reversible capacity of the battery.

[0005] In summary, although O3 phase layered oxide cathode materials have potential in low-voltage operation, they still face significant challenges in terms of cycle performance and capacity utilization. Summary of the Invention

[0006] The purpose of this invention is to provide sodium-ion layered oxide cathode materials and their preparation methods, cathode sheets, batteries, and electrical devices to solve the problems mentioned in the background art.

[0007] The technical solution adopted in this invention includes: a method for preparing sodium-ion layered oxide cathode material, comprising the following steps:

[0008] Sodium-electric layered oxide matrix raw material is sintered in an oxygen-containing atmosphere to obtain sodium-electric layered oxide matrix material;

[0009] Sodium-electric layered oxide matrix material and sodium citrate were sintered in an inert atmosphere to prepare sodium-electric layered oxide cathode material;

[0010] The chemical formula of the sodium-electric layered oxide matrix material is Na. x M y Ni a Mn b Fe c Q z O2, M is one or more of Ca, K, and Li, Q is one or more of Cu, Sn, Mg, Al, Li, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo, W, and B, a+b+c+y+z=1, 0.9 <x<1.0。

[0011] Preferably, the mass ratio of the sodium-electric layered oxide matrix material to sodium citrate is 1:(0.1%~0.3%).

[0012] Preferably, 0 ≤ y ≤ 0.05, 0.2 <a<0.3,0.2<b<1,0.2<c<1,0≤z≤0.05。

[0013] Preferably, the sodium-ionized layered oxide matrix raw material includes a sodium source, an M source, a nickel source, a manganese source, an iron source, and a Q source. The M source includes one or more of Li2CO3, LiOH, LiF, K2CO3, CaCO3, and CaO. The Q source includes one or more of CuO, SnO2, MgO, MgCO3, Al2O3, ZnO, TiO2, Nb2O5, MoO3, Y2O3, Ta2O5, WO3, BaO, BaCO3, SrCO3, SrO, H3BO3, and B2O3.

[0014] Preferably, when preparing the sodium-electric layered oxide matrix material, the sodium-electric layered oxide matrix raw material is sintered at 400~600℃ for 4h, and then sintered at 850~1000℃ for 6h~30h; when preparing the sodium-electric layered oxide cathode material, the sintering temperature is 300~500℃ and the sintering time is 2h~4h.

[0015] Preferably, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere.

[0016] The technical solution of the present invention also includes: a sodium-electric layered oxide cathode material prepared by the above method, wherein the coating layer of the sodium-electric layered oxide cathode material contains amorphous carbon and sodium carbonate.

[0017] The technical solution of the present invention also includes: a positive electrode sheet, wherein the positive electrode sheet contains the above-mentioned sodium-ion layered oxide positive electrode material.

[0018] The technical solution of the present invention also includes: a battery, wherein the battery contains the above-mentioned positive electrode sheet.

[0019] The technical solution of the present invention also includes: an electrical device, wherein the electrical device contains the aforementioned battery.

[0020] The beneficial effects of this invention include at least the following: through the synergistic effect of in-situ thermal decomposition coating of sodium citrate and dual-site doping of alkali metal layer and transition metal layer, a sodium-ion layered oxide cathode material with high first-cycle charge specific capacity, high discharge equal voltage and excellent cycle stability in the low voltage range is prepared. This effectively solves the problems of sodium loss, slow kinetics and structural instability of O3 phase materials in low voltage applications, and provides a high-performance cathode material solution for low-temperature start-stop and other scenarios. Attached Figure Description

[0021] Figure 1 The image shows the XRD pattern of the sodium-ion layered oxide cathode material prepared according to Embodiment 2 of the present invention.

[0022] Figure 2 The graphs show the first-week charge-discharge performance test results for some embodiments and comparative examples of the present invention. Detailed Implementation

[0023] The present invention will be further described below with reference to embodiments and accompanying drawings:

[0024] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing specific embodiments and comparative examples only and are not intended to limit the scope of protection of this invention. It should be specifically noted that the same organic structure may have multiple names, and all such structures fall within the scope of this patent.

[0025] Unless otherwise defined, the raw materials, reagents, etc. used in the following examples can be purchased commercially or prepared according to reported methods.

[0026] In a first aspect of the present invention, a method for preparing a sodium-ion layered oxide cathode material is provided, specifically comprising the following steps:

[0027] Sodium-electric layered oxide matrix raw material is sintered in an oxygen-containing atmosphere to obtain sodium-electric layered oxide matrix material. The chemical formula of the sodium-electric layered oxide matrix material is Na. x M y Ni a Mn b Fe c Q zO2, M is one or more of Ca, K, and Li, Q is one or more of Cu, Sn, Mg, Al, Li, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo, W, and B, a+b+c+y+z=1, 0.9 <x<1.0。

[0028] Sodium-ion layered oxide matrix material and sodium citrate were sintered in an inert atmosphere to prepare sodium-ion layered oxide cathode material.

[0029] In preparing sodium-electric layered oxide matrix materials, this scheme utilizes elements with large ionic radii such as Ca, K, and Li to dope the alkali metal layer, thereby broadening the sodium ion transport path and suppressing interlayer slip, thus improving the cycling stability of the material. Simultaneously, by controlling the ratio of transition metal elements such as Ni, Fe, and Mn, and doping the transition metal layer with elements such as Cu, Sn, Mg, Al, Li, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo, W, and B, the charge distribution is adjusted, the metal-oxygen bonding strength is enhanced, and the Jam-Taylor distortion is suppressed, thereby improving the first-cycle discharge voltage and energy density of the material. The obtained sodium-ion layered oxide matrix material was co-sintered with sodium citrate in an inert atmosphere. Sodium citrate thermally decomposed to generate sodium carbonate and amorphous carbon. Sodium carbonate participates in the formation of the solid electrolyte interfacial film on the negative electrode surface during the first charge-discharge process, reducing the irreversible consumption of sodium ions in the sodium-ion layered oxide matrix material and acting as a sodium replenisher to improve the first-cycle charge specific capacity. Amorphous carbon improves the material's interfacial conductivity and ion transport capacity, while also isolating sodium carbonate from external moisture, preventing sodium carbonate hydrolysis and its impact on the material's slurry preparation performance. The resulting sodium-ion layered oxide positive electrode material exhibits high first-cycle discharge average voltage and high first-charge performance within a low voltage range, while also demonstrating good cycle stability.

[0030] The aforementioned sodium-ionized layered oxide matrix raw materials include a sodium source, an M source, a nickel source, a manganese source, an iron source, and a Q source. The sodium source can be one or more of Na₂CO₃, NaHCO₃, and NaOH, preferably Na₂CO₃; the M source can be one or more of Li₂CO₃, LiOH, LiF, K₂CO₃, CaCO₃, and CaO, preferably CaCO₃ or LiOH; the nickel, manganese, and iron sources can be oxides of the corresponding metal elements, or precursors containing Ni, Mn, and Fe hydroxides prepared using mature processes; the Q source can be one or more of CuO, SnO₂, MgO, MgCO₃, Al₂O₃, ZnO, TiO₂, Nb₂O₅, MoO₃, Y₂O₃, Ta₂O₅, WO₃, BaO, BaCO₃, SrCO₃, SrO, H₃BO₃, and B₂O₃, preferably ZnO or TiO₂.

[0031] Based on the above raw material selection and preferred solutions, the present invention further determines a preferred stoichiometric ratio range by adjusting the doping amount of each element and performing comparative testing of electrochemical properties. When 0≤y≤0.05, 0.2<a<0.3, 0.2<b<1, 0.2<c<1, and 0≤z≤0.05 are satisfied, the obtained layered oxide positive electrode material for sodium-ion batteries can achieve excellent comprehensive electrochemical performance in the low-voltage operating range. Within this composition range, the doping of element M with a large ionic radius in the alkali metal layer can not only exert a "pillar effect" to stabilize the crystal structure and widen the diffusion channels for sodium ions, but also avoid capacity degradation or structural distortion caused by excessive doping. At the same time, by controlling the molar coefficients of Ni, Mn, and Fe within the preferred range, combined with the introduction of element Q such as Cu, Sn, Mg, Al, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo, W, B for doping, it is beneficial to adjust the charge distribution, enhance the metal-oxygen bonding strength, and suppress structural distortion caused by the Jahn-Teller effect of ions such as Mn³⁺. If the ratio of Ni, Mn, and Fe deviates from the preferred range, it will be difficult to form a stable O3-phase layered structure, or cause a significant decrease in one or more of the properties including operating voltage, specific capacity, and cycle stability. The combined effect of the above element doping and ratio regulation enables the obtained layered oxide positive electrode material for sodium-ion batteries to have high first-cycle average discharge voltage, high specific capacity and excellent cycle stability.

[0032] When preparing the layered oxide base material for sodium-ion batteries, the preferred sintering conditions for the raw materials of the layered oxide base material for sodium-ion batteries are: under an oxygen-containing atmosphere (such as air atmosphere) of 0~2MPa, at a heating rate of 5°C / min, raise the temperature from room temperature to 400~600°C for sintering for 4h, then raise the temperature to 850~1000°C for sintering for 6h~30h, and finally cool naturally to room temperature with the furnace, with the ambient humidity being less than 20wt% during the cooling process. Controlling the sintering conditions within the above preferred range is beneficial to obtaining the layered oxide base material for sodium-ion batteries with good crystallinity, stable structure and excellent electrochemical performance.

[0033] In some preferred embodiments, the mass ratio of sodium-ion layered oxide matrix material to sodium citrate is 1:(0.1%~0.3%). Within this range, the amount of sodium carbonate generated by the thermal decomposition of sodium citrate is moderate. This effectively participates in the formation of the solid electrolyte interfacial film on the negative electrode surface and plays a role in sodium replenishment, reducing the irreversible consumption of sodium ions in the matrix material during the first charge and discharge process. It also avoids excessive alkalinity on the material surface, decreased slurry stability, or difficulties in electrode processing due to excessive sodium carbonate. Simultaneously, the amount of amorphous carbon generated is also at a reasonable level, which is beneficial for improving the interfacial conductivity and ion conduction capacity of the material particles. If the sodium citrate addition ratio is less than 0.1 wt%, the sodium replenishment effect and interfacial modification effect are not significant; if the addition ratio is greater than 0.3 wt%, excessive sodium carbonate and amorphous carbon may reduce the proportion of active material in the positive electrode material, thus affecting the overall energy density of the battery. Therefore, controlling the mass ratio within the above-mentioned preferred range can fully utilize the sodium replenishment and interfacial modification effects while taking into account the material's processing performance and the battery's overall electrochemical performance.

[0034] It is important to note that the thermal decomposition of sodium citrate must be carried out in an inert atmosphere. If heated in an oxygen-containing atmosphere (such as air), sodium citrate will convert to carbon dioxide and cannot form sodium carbonate, thus losing its sodium replenishment function and its ability to participate in the formation of the negative electrode interface film. Only under the protection of an inert atmosphere can sodium citrate thermally decompose according to the expected pathway to generate sodium carbonate and amorphous carbon, thereby playing multiple roles such as reducing irreversible sodium ion consumption, increasing the specific capacity during the first charge cycle, improving interfacial conductivity, and isolating moisture. The preferred inert atmospheres are nitrogen or argon, as these atmospheres are widely available, low in cost, and easily implemented in industrial production.

[0035] When preparing sodium-ion battery layered oxide cathode materials, the preferred sintering conditions for the sodium-ion battery layered oxide matrix material and sodium citrate are as follows: heating from room temperature to 300-500°C at a heating rate of 2°C / min under an inert atmosphere (e.g., nitrogen atmosphere with a purity ≥99.99%), followed by holding at that temperature for 2-4 hours, and finally natural cooling to room temperature. Controlling the sintering conditions within the above-mentioned preferred range allows for the acquisition of sodium-ion battery layered oxide cathode materials with uniform surface coating, significant sodium replenishment effect, and good interfacial conductivity.

[0036] In a second aspect, the present invention provides a sodium-electric layered oxide cathode material prepared by the above method. This sodium-electric layered oxide cathode material is a shell-core structure polycrystalline particle with a median particle size of 3 μm to 8 μm and a water content of less than 500 ppm. The shell structure of this sodium-electric layered oxide cathode material is a coating layer formed by the thermal decomposition of sodium citrate, which contains amorphous carbon and sodium carbonate. The core structure is a sodium-electric layered oxide matrix material with a crystal structure of O3 phase, hexagonal crystal system, R-3m space group, and preferably the chemical formula Na.0.98 Ca 0.03 Ni 0.23 Fe 0.34 Mn 0.35 Ti 0.02 Zn 0.03 O2 or Na 0.98 Li 0.02 Ni 0.23 Fe 0.345 Mn 0.355 Ti 0.02 Zn 0.03 O2. Tests showed that this sodium-ion layered oxide cathode material exhibited excellent electrochemical performance, with an average discharge voltage of no less than 3.06V in the first cycle within a low voltage range of 2.0~3.7V, a first-cycle charge specific capacity of no less than 108mAh / g at a 0.1C rate, and a capacity retention rate of no less than 94% after 50 cycles at a 1C rate.

[0037] A third aspect of the present invention provides a positive electrode sheet containing the above-described sodium-ion layered oxide positive electrode material.

[0038] In a fourth aspect, the present invention provides a battery comprising the above-described positive electrode sheet.

[0039] A fifth aspect of the present invention provides an electrical device comprising the aforementioned battery.

[0040] The following are specific embodiments and comparative examples of the present invention.

[0041] Example 1

[0042] (1) Preparation of Na 0.98 Ca 0.03 Ni 0.23 Fe 0.34 Mn 0.35 Ti 0.02 Zn 0.03 Sodium-electric layered oxide matrix material of O2

[0043] Sodium-ionized layered oxide matrix raw materials such as Na2CO3, NiO, Mn2O3, Fe2O3, ZnO, TiO2, and CaCO3 are taken according to the element stoichiometry in the above chemical formula and mixed evenly using a high-speed mixer.

[0044] The mixed sodium-electric layered oxide matrix raw material was sintered in an air atmosphere furnace in stages. First, it was sintered at 500°C for 4 hours, then at 900°C for 24 hours, and finally cooled with the furnace to obtain the sodium-electric layered oxide matrix material.

[0045] (2) Preparation of sodium-ion layered oxide cathode material

[0046] Sodium-ion layered oxide matrix material and sodium citrate were taken at a mass ratio of 1:0.1%, mixed uniformly, and then transferred to a nitrogen atmosphere furnace for sintering. The temperature was increased from room temperature to 400°C at a heating rate of 3°C / min, and then held for sintering for 3 hours. Finally, the material was cooled in the furnace to obtain sodium-ion layered oxide cathode material.

[0047] Example 2

[0048] (1) Preparation of Na 0.98 Ca 0.03 Ni 0.23 Fe 0.34 Mn 0.35 Ti 0.02 Zn 0.03 Sodium-electric layered oxide matrix material of O2

[0049] Sodium-ionized layered oxide matrix raw materials such as Na2CO3, NiO, Mn2O3, Fe2O3, ZnO, TiO2, and CaCO3 are taken according to the element stoichiometry in the above chemical formula and mixed evenly using a high-speed mixer.

[0050] The mixed sodium-electric layered oxide matrix raw material was sintered in an air atmosphere furnace in stages. First, it was sintered at 500°C for 4 hours, then at 900°C for 24 hours, and finally cooled with the furnace to obtain the sodium-electric layered oxide matrix material.

[0051] (2) Preparation of sodium-ion layered oxide cathode material

[0052] Sodium-ion layered oxide matrix material and sodium citrate were taken at a mass ratio of 1:0.2%, mixed uniformly, and then transferred to a nitrogen atmosphere furnace for sintering. The temperature was increased from room temperature to 400°C at a heating rate of 3°C / min, and then held for sintering for 3 hours. Finally, the material was cooled with the furnace to obtain sodium-ion layered oxide cathode material.

[0053] Example 3

[0054] (1) Preparation of Na 0.98 Ca 0.03 Ni 0.23 Fe 0.34 Mn 0.35 Ti 0.02 Zn 0.03 Sodium-electric layered oxide matrix material of O2

[0055] Sodium-ionized layered oxide matrix raw materials such as Na2CO3, NiO, Mn2O3, Fe2O3, ZnO, TiO2, and CaCO3 are taken according to the element stoichiometry in the above chemical formula and mixed evenly using a high-speed mixer.

[0056] The mixed sodium-electric layered oxide matrix raw material was sintered in an air atmosphere furnace in stages. First, it was sintered at 500°C for 4 hours, then at 900°C for 24 hours, and finally cooled with the furnace to obtain the sodium-electric layered oxide matrix material.

[0057] (2) Preparation of sodium-ion layered oxide cathode material

[0058] Sodium-ion layered oxide matrix material and sodium citrate were taken at a mass ratio of 1:0.3%, mixed uniformly, and then transferred to a nitrogen atmosphere furnace for sintering. The temperature was increased from room temperature to 400°C at a heating rate of 3°C / min, and then held for sintering for 3 hours. Finally, the sodium-ion layered oxide cathode material was obtained by furnace cooling.

[0059] Example 4

[0060] (1) Preparation of Na 0.98 Li 0.02 Ni 0.23 Fe 0.345 Mn 0.355 Ti 0.02 Zn 0.03 Sodium-electric layered oxide matrix material of O2

[0061] Sodium-ionized layered oxide matrix raw materials such as Na2CO3, NiO, Mn2O3, Fe2O3, TiO2, LiOH, and ZnO are taken according to the element stoichiometry in the above chemical formula and mixed evenly using a high-speed mixer.

[0062] The mixed sodium-electric layered oxide matrix raw material was sintered in an air atmosphere furnace in stages. First, it was sintered at 500°C for 4 hours, then at 900°C for 24 hours, and finally cooled with the furnace to obtain the sodium-electric layered oxide matrix material.

[0063] (2) Preparation of sodium-ion layered oxide cathode material

[0064] Sodium-ion layered oxide matrix material and sodium citrate were taken at a mass ratio of 1:0.2%, mixed uniformly, and then transferred to a nitrogen atmosphere furnace for sintering. The temperature was increased from room temperature to 400°C at a heating rate of 3°C / min, and then held for sintering for 3 hours. Finally, the material was cooled with the furnace to obtain sodium-ion layered oxide cathode material.

[0065] Comparative Example 1

[0066] (1) Preparation of Na 0.98 Ca 0.03 Ni 0.23 Fe 0.34 Mn 0.35 Ti 0.02 Zn 0.03 Sodium-electric layered oxide matrix material of O2

[0067] Using a commercially available spherical hydroxide precursor with an elemental stoichiometric ratio of Ni:Fe:Mn=25:37:38 as raw material, the spherical hydroxide precursor, Na2CO3, ZnO, TiO2, CaCO3 and other sodium-electric layered oxide matrix raw materials are taken according to the elemental stoichiometric ratio in the above chemical formula and mixed evenly by a high-speed mixer.

[0068] The mixed sodium-electric layered oxide matrix raw material was sintered in an air atmosphere furnace in stages. First, it was sintered at 500°C for 4 hours, then at 900°C for 24 hours, and finally cooled with the furnace to obtain the sodium-electric layered oxide matrix material.

[0069] (2) Preparation of sodium-ion layered oxide cathode material

[0070] Sodium-ion layered oxide matrix material and sodium citrate were taken at a mass ratio of 1:0.2%, mixed uniformly, and then transferred to a nitrogen atmosphere furnace for sintering. The temperature was increased from room temperature to 400°C at a heating rate of 3°C / min, and then held for sintering for 3 hours. Finally, the material was cooled with the furnace to obtain sodium-ion layered oxide cathode material.

[0071] Comparative Example 2

[0072] The only difference from Example 2 is that sodium citrate was not added in step (2) of Comparative Example 2.

[0073] Comparative Example 3

[0074] The only difference from Example 4 is that sodium citrate was not added in step (2) of Comparative Example 3.

[0075] Comparative Example 4

[0076] Preparation of chemical formula Na 0.98 Ni 0.25 Fe 0.37 Mn 0.38 O2 sodium-ionized layered oxide cathode material.

[0077] According to the elemental stoichiometric ratio Na:Ni:Fe:Mn=0.98:0.25:0.37:0.38, Na2CO3, NiO, Mn2O3 and Fe2O3 were taken and mixed evenly. After mixing, they were transferred to an air atmosphere furnace for stepwise sintering. First, sintering was carried out at 500℃ for 4 hours, then at 900℃ for 24 hours, and then at 400℃ for 3 hours. Finally, the furnace was cooled to room temperature to obtain sodium-ion layered oxide cathode material.

[0078] Characterization and testing:

[0079] The sodium-ion layered oxide cathode material prepared in Example 2 was subjected to XRD analysis. The test conditions were: Cu-Kα target, emission wavelength λ = 0.154 nm, scanning voltage 40 kV, current 50 mA, using a step-scan method, and a scanning range of 10°~80°. The obtained XRD pattern is shown below. Figure 1 As shown, the results indicate that the material has typical layered oxide crystal structure characteristics.

[0080] The sodium-ionized layered oxide cathode materials prepared in Examples 1-4 and Comparative Examples 1-4 were used to prepare test batteries according to the following method: The sodium-ionized layered oxide cathode material was mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 90:5:5, and an appropriate amount of N-methylpyrrolidone was added as a dispersant. The mixture was then ground until homogeneous to obtain a slurry. The slurry was uniformly coated onto one side of an aluminum foil and vacuum dried at 120°C for 10 hours. After drying, the electrode sheet was rolled by a roller press and then cut into circular electrode sheets with a diameter of 1.3 cm using a slicing machine. The loading of active material was controlled at 10 mg·cm³. -2 Approximately. CR2032 coin cells were assembled in an argon atmosphere glove box with a water pressure ≤0.1ppm and an oxygen partial pressure ≤0.1ppm. Sodium metal was used as the counter electrode, and the electrolyte consisted of 1M NaPF6 as the solute and EC and DEC as the solvent in a 1:1 volume ratio.

[0081] Electrochemical performance tests were conducted on the prepared test cells. A constant current charge-discharge mode was used, and the cells were tested at room temperature. First, the cells were charged at a constant current density of 15 mA / g to 3.7 V (vs. Na / Na⁺), then discharged at the same current density to 2.0 V (vs. Na / Na⁺). The specific capacity, initial coulombic efficiency, and average voltage of the first discharge cycle were recorded. Then, a constant current charge-discharge cycle of 50 mA / g was performed for 50 cycles, with a voltage range of 2.0–3.7 V. The test results are shown in Table 1 and Appendix. Figure 2 As shown.

[0082] Table 1

[0083] First week charging capacity (mAh / g) Discharge specific capacity in the first week (mAh / g) First week Coulomb efficiency Equal discharge voltage (V) during the first week 50-cycle capacity retention Example 1 108.2 106.9 98.80% 3.07 98.55% Example 2 112.5 108.1 96.09% 3.06 96.60% Example 3 113.5 107.8 94.98% 3.07 94.13% Example 4 111.8 107.5 96.15% 3.06 95.22% Comparative Example 1 112.5 108.9 96.80% 3.07 97.89% Comparative Example 2 106.5 105.7 99.25% 3.08 98.44% Comparative Example 3 107.6 105.1 97.68% 3.06 97.94% Comparative Example 4 106.8 100.7 94.29% 3.04 76.64%

[0084] Based on Table 1 and Appendix Figure 2 Comparing Example 2 with Comparative Example 2, and Example 4 with Comparative Example 3, it can be seen that under the same matrix material conditions, the sample coated with sodium citrate has a significantly higher first-week charge specific capacity than the uncoated sample, indicating that the sodium carbonate generated by the thermal decomposition of sodium citrate plays an effective role in sodium replenishment. Comparing Example 1, Example 2, and Example 3, it can be seen that as the amount of sodium citrate increases, the first-week charge specific capacity gradually increases, but the cycle stability shows a decreasing trend, indicating that there is an optimal range for the feed ratio. The 0.2% feed ratio used in Example 2 achieves the best balance between sodium replenishment effect and cycle stability.

[0085] Comparing Example 1 and Comparative Example 4, it can be seen that the cycling capacity retention is significantly improved through dual-site doping of the alkali metal layer and the transition metal layer, demonstrating the significant effect of the doping strategy in suppressing structural distortion and enhancing crystal stability. Comparing Example 2 and Comparative Example 1, it can be seen that the technical solution of this invention has good applicability to both oxide raw material routes and hydroxide precursor routes, which is beneficial for industrial production.

[0086] In summary, this invention successfully prepared a sodium-based layered oxide cathode material with high first-cycle charge specific capacity, high first-cycle discharge average voltage, and excellent cycle stability in the low-voltage range through the synergistic effect of in-situ thermal decomposition coating of sodium citrate and dual-site doping of alkali metal and transition metal layers. This effectively solves the problems of sodium loss and structural instability of O3 phase materials in low-voltage applications, and provides a high-performance cathode material solution for scenarios such as low-temperature start-stop.

[0087] It should be understood that the specific embodiments described above are merely illustrative or explanatory of the principles of the invention and do not constitute a limitation thereof. Therefore, any modifications, equivalent substitutions, improvements, etc., made without departing from the spirit and scope of the invention should be included within the protection scope of the invention. Furthermore, the appended claims are intended to cover all variations and modifications falling within the scope and boundaries of the claims, or equivalent forms of such scope and boundaries.

Claims

1. A method for preparing sodium-ion battery layered oxide cathode material, characterized in that, Including the following steps: Sodium-electric layered oxide matrix raw material is sintered in an oxygen-containing atmosphere to obtain sodium-electric layered oxide matrix material; Sodium-electric layered oxide matrix material and sodium citrate were sintered in an inert atmosphere to prepare sodium-electric layered oxide cathode material; The chemical formula of the sodium-electric layered oxide matrix material is Na. x M y Ni a Mn b Fe c Q z O2, M is one or more of Ca, K, and Li, Q is one or more of Cu, Sn, Mg, Al, Li, Zn, Ti, Zr, Cr, Sr, Ba, Nb, Mo, W, and B, a+b+c+y+z=1, 0.9 <x<1.0。 2. The method for preparing the sodium-ion layered oxide cathode material according to claim 1, characterized in that, The mass ratio of the sodium-electric layered oxide matrix material to sodium citrate is 1:(0.1%~0.3%).

3. The method for preparing the sodium-ion battery layered oxide cathode material according to claim 1, characterized in that, 0≤y≤0.05, 0.2 <a<0.3,0.2<b<1,0.2<c<1,0≤z≤0.05。 4. The method for preparing the sodium-ion layered oxide cathode material according to claim 3, characterized in that, The sodium-electric layered oxide matrix raw material includes a sodium source, an M source, a nickel source, a manganese source, an iron source, and a Q source. The M source includes one or more of Li2CO3, LiOH, LiF, K2CO3, CaCO3, and CaO. The Q source includes one or more of CuO, SnO2, MgO, MgCO3, Al2O3, ZnO, TiO2, Nb2O5, MoO3, Y2O3, Ta2O5, WO3, BaO, BaCO3, SrCO3, SrO, H3BO3, and B2O3.

5. The method for preparing the sodium-ion layered oxide cathode material according to any one of claims 1-4, characterized in that, When preparing the sodium-electric layered oxide matrix material, the sodium-electric layered oxide matrix raw material is sintered at 400~600℃ for 4h, and then sintered at 850~1000℃ for 6h~30h; when preparing the sodium-electric layered oxide cathode material, the sintering temperature is 300~500℃ and the sintering time is 2h~4h.

6. The method for preparing the sodium-ion battery layered oxide cathode material according to claim 5, characterized in that, The inert atmosphere is a nitrogen atmosphere or an argon atmosphere.

7. A sodium-electric layered oxide cathode material prepared by the method for preparing sodium-electric layered oxide cathode materials according to any one of claims 1-6, characterized in that, The coating layer of the sodium-ion layered oxide cathode material contains amorphous carbon and sodium carbonate.

8. A positive electrode sheet, characterized in that, The positive electrode sheet contains the sodium-electric layered oxide positive electrode material as described in claim 7.

9. A battery, characterized in that, The battery contains the positive electrode sheet as described in claim 8.

10. An electrical appliance, characterized in that, The electrical device contains the battery as described in claim 9.